ExoDS: a versatile exosome-based drug delivery platform to target cancer cells and cancer stem cells - Paul, Swastika; Bhagat, Shrikrishna; Dash, Lipsa; Mohapatra, Himadri Das; Jena, Sarita; Verma, Suresh K.; Dutta, Abhishek (Frontiers in Bioengineering and Biotechnology, 2024)
Chemotherapy drugs like doxorubicin, is widely used in middle-income countries around the world to treat cancers including breast cancer. Although they are toxic, they are still widely used to treat cancer. Delivering chemotherapy drugs directly to cancer cells to reduce side-effects still remains a challenge. Moreover, modern research gave rise to cancer stem cell theory which implicated cancer stem cells in tumor initiation, progression and relapse. This makes it imperative to target cancer stem cells to achieve complete remission. Our work highlights the development of an exosome-based targeted drug delivery vehicle. These exosomes were isolated from mature dendritic cells (mDCs) and encapsulated with doxorubicin (ExoDS). Our results showed that ExoDS specifically targeted breast cancer cells and breast cancer stem cells. Further analysis revealed that ExoDS did not induce any significant apoptosis in healthy mammary cells and peripheral blood mononuclear cells (PBMCs) isolated from healthy individuals and breast cancer patients. ExoDS was also found to target circulating tumor cells (CTCs) isolated from patient blood. ExoDS also showed equal efficiency as compared to free doxorubicin invivo. We also observed that ExoDS reduced expression of cancer stem cells markers in murine tumor tissues. Altogether, this work provides novel insights on how mDC-derived exosomes can be used to specifically target cancer cells and cancer stem cells.